The Altered Anatomical Distribution of ACE2 in the Brain With Alzheimer’s Disease Pathology - Cui, Huan; Su, Si; Cao, Yan; Ma, Chao; Qiu, Wenying (Frontiers in Cell and Developmental Biology, 2021)
The whole world is suffering from the coronavirus disease 2019 (COVID-19) pandemic, induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) through angiotensin-converting enzyme 2 (ACE2). Neurological manifestations in COVID-19 patients suggested the invasion of SARS-CoV-2 into the central nervous system. The present study mapped the expression level of ACE2 in 12 brain regions through immunohistochemistry and detected ACE2 in endothelial cells and non-vascular cells. The comparison among brain regions found that pons, visual cortex, and amygdala presented a relatively high level of ACE2. In addition, this study demonstrates that the protein level of ACE2 was downregulated in the basal nucleus, hippocampus and entorhinal cortex, middle frontal gyrus, visual cortex, and amygdala of the brain with Alzheimer's disease (AD) pathology. Collectively, our results suggested that ACE2 was expressed discriminatorily at different human brain regions, which was downregulated in the brain with AD pathology. This may contribute to a comprehensive understanding of the neurological symptoms caused by the SARS-CoV-2 and provide clues for further research on the relationship between the COVID-19 and AD.